ANALYSIS OF THE RELATIONSHIP BETWEEN THE COVID-19 PANDEMIC AND ELECTRICITY CONSUMPTION IN SOUTH SUMATRA USING A LINEAR REGRESSION APPROACH - Amanda Elsha Novia Nabila; Nabila, Hendri Ridwan Ramadhan; Haikal Ilhamullah Pramuaji; Sinyoardi Winarno; Ahnaf Hifzhan Robbani (Indonesian Journal of Electrical Engineering and Electronics, 2023)
Electrical energy is one of the major needs of society and an important economic resource required for various activities. With population growth and development, power demand will increase in the future, the development of industry and technology, and the development of the educational world. This study focuses on estimating the total amount of energy sold based on the population of South Sumatra from 2014 to 2021. The methods used are simple linear regression and correlation methods. Regression analysis is used to investigate and measure statistical relationships that occur between two or more variables. Judging from the population calculation data for 2020-2021 and data from BPS South Sumatra, the calculated population is much greater than the population in the BPS data. This also applies to the total amount of energy data (with KWh units), for the total amount of energy in 2020 of 5,308.450000 KWh in the expected range of values, this is in the range of 5,215,695,859 < y < 5,626,645,251 while for the total energy 2021 according to PLN data 5,593,930,000 KWh which is in the predicted range value, which is in the range of 5,290,517,098 < y < 6,284,994,826. This is because population growth affects the increase in total energy consumption